Changes in forebrain function from waking to REM sleep in depression: preliminary analyses [of 18F]FDG PET studies - Nofzinger, Eric A.; Nichols, Thomas E.; Meltzer, Carolyn C.; Price, Julie; Steppe, Doris A.; Miewald, Jean M.; Kupfer, David J.; Moore, Robert Y. (Psychiatry research, 1999)
Based on recent functional brain imaging studies of healthy human REM sleep, we hypothesized that alterations in REM sleep in mood disorder patients reflect a functional dysregulation within limbic and paralimbic forebrain structures during that sleep state. Six unipolar depressed subjects and eight healthy subjects underwent separate [ 18F]2-fluoro-2-deoxy- d-glucose ([ 18F]FDG) PET scans during waking and during their first REM period of sleep. Statistical parametric mapping contrasts were performed to detect changes in relative regional cerebral glucose metabolism (rCMRglu) from waking to REM sleep in each group as well as interactions in patterns of change between groups. Clinical and EEG sleep comparisons from an undisturbed night of sleep were also performed. In contrast to healthy control subjects, depressed patients did not show increases in rCMRglu in anterior paralimbic structures in REM sleep compared to waking. Depressed subjects showed greater increases from waking to REM sleep in rCMRglu in the tectal area and a series of left hemispheric areas including sensorimotor cortex, inferior temporal cortex, uncal gyrus-amygdala, and subicular complex than did the control subjects. These observations indicate that changes in limbic and paralimbic function from waking to REM sleep differ significantly from normal in depressed patients.